2010
DOI: 10.1179/147683010x12611460764002
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous neurocognitive retrieval of patients with sub-acute ischemic stroke is associated with dietary protein intake

Abstract: In sub-acute strokes, patient neurological and cognitive retrieval could positively be associated with protein intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In further support of these data, we recently documented a positive correlation between spontaneous improvement of neurocognitive deficits and dietary protein intake and a negative correlation with the dietary carbo‐hydrate:protein ratio in patients with subacute stroke 23 …”
Section: Suppression Of Brain Protein Synthesis and Nutrition Intervesupporting
confidence: 56%
See 2 more Smart Citations
“…In further support of these data, we recently documented a positive correlation between spontaneous improvement of neurocognitive deficits and dietary protein intake and a negative correlation with the dietary carbo‐hydrate:protein ratio in patients with subacute stroke 23 …”
Section: Suppression Of Brain Protein Synthesis and Nutrition Intervesupporting
confidence: 56%
“…In further support of these data, we recently documented a positive correlation between spontaneous improvement of neurocognitive deficits and dietary protein intake and a negative correlation with the dietary carbohydrate:protein ratio in patients with subacute stroke. 23 When considering explanations for the positive influence of protein on brain function, the first point to keep in mind is that the types of cerebral proteins, 24 and hence the amino acid profile in the brain, 25 are influenced by the types of dietary proteins. We proposed 11,13,22,23 that multiple mechanisms may account for the efficacy of protein supplementation on brain function of patients with subacute stroke.…”
Section: Suppression Of Brain Protein Synthesis and Nutrition Intervementioning
confidence: 99%
See 1 more Smart Citation
“…Neurotransmitters are synthesized from amino acids, and the synthesis of new proteins is required for the formation of new cortical networks 5 . Of particular significance is that trials and observational data in adult patients with stroke and traumatic brain injury have demonstrated that protein supplementation results in improved motor and cognitive outcomes 3 , 4 , 6 , 7 . Infants and children with cerebral palsy are known to be at high risk for growth failure 8 .…”
mentioning
confidence: 99%
“…5 Of particular significance is that trials and observational data in adult patients with stroke and traumatic brain injury have demonstrated that protein supplementation results in improved motor and cognitive outcomes. 3,4,6,7 Infants and children with cerebral palsy are known to be at high risk for growth failure. 8 There is, however, a paucity of data linking the evidence of dietary protein and growth outcomes in this population.…”
mentioning
confidence: 99%